1975
DOI: 10.1093/ajcn/28.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral contraceptive steroids on vitamin and lipid levels in serum

Abstract: The results of a comprehensive study to determine the effects of oral contraceptive agents on nutrient metabolism have been reported. The group of women using oral contraceptive agents was found to have significantly higher levels of hemoglobin, packed cell volume, serum vitamin A, total lipids, triglycerides, vitamin E, and alpha1-protein and significantly lower levels of serum and red cell folacin, vitamin B12 and albumin. The biological significance of many of these differences has not been elucidated satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The tendency for smoking to be associated with an increased retinol and decreased fl-carotene level has been reported previously (Yeung, 1976;Witter et al, 1982;Salonen et al, 1985) although some data sets are not consistent with such a relationship for retinol (Wald, personal communication). A positive effect of OC usage on retinol concentrations has also been found previously Gal et al, 1971;Gal & Parkinson, 1973;Yeung, 1974Yeung, , 1976Smith et al, 1975;Yeung & Chan, 1975), but there is some controversy as to whether it affects fl-carotene (Yeung & Chan, 1975).…”
Section: Discussionsupporting
confidence: 52%
“…The tendency for smoking to be associated with an increased retinol and decreased fl-carotene level has been reported previously (Yeung, 1976;Witter et al, 1982;Salonen et al, 1985) although some data sets are not consistent with such a relationship for retinol (Wald, personal communication). A positive effect of OC usage on retinol concentrations has also been found previously Gal et al, 1971;Gal & Parkinson, 1973;Yeung, 1974Yeung, , 1976Smith et al, 1975;Yeung & Chan, 1975), but there is some controversy as to whether it affects fl-carotene (Yeung & Chan, 1975).…”
Section: Discussionsupporting
confidence: 52%
“…It is likely that the inconsistency between these early studies may be due to lack of control of potentially confounding variables. For example, in most studies there were no controls for dietary folate intake, vitamin supplement use, smoking, or alcohol use 39–57 . In addition, other factors not considered by many investigators include differences in the specific type of hormone used in the OCs, 58,59 compliance with the OC regimen, 44,58,59 and duration of OC use 50,58 .…”
mentioning
confidence: 99%
“…More recently conducted studies, designed to evaluate the effect of OC use on folate status, have included measures of RBC folate concentration; however, as with studies measuring only serum folate concentration, the results have been equivocal 46–48,50,51,60–62 . In the studies from which it was concluded that OC use negatively affected folate status, none controlled for all potentially confounding variables, including differences in dietary intake and use of folic acid‐containing supplements 46,48,60,62 . Of those studies that controlled for dietary intake, with one exception, 62 no difference in RBC folate concentration between OC and non‐OC users was detected 47,50,58–61 .…”
mentioning
confidence: 99%
“…17 Early observational studies in OC users conducted in the 1960s led to the hypothesis that the use of synthetic hormones may negatively influence folate status. 18,19 Subsequently, multiple studies on healthy women were performed: in all these cases, the dietary intake has been judged from adequate to good. 7,[20][21][22] Some Authors suggested that the absorption of naturallyoccurring food folate may be impaired in women using OC.…”
Section: Folate Statusmentioning
confidence: 99%